Corporate social responsibility and sustainable development in the UAE financial service sector: Strategic integration - Odeh, Mohmmad Husam; Jawabri, Adnan (International Journal of Innovative Research and Scientific Studies, 2025)
The study examines the role of Corporate Social Responsibility (CSR) in running sustainable development within the UAE’s financial services sector, which focuses on the mediation effect of strategic integration. Using PLS-SEM analysis of survey data from 235 professionals, conclusions reveal a significant positive relationship between CSR practices and sustainable development (β = 0.45, P < 0.01), enhancing this relationship with strategic integration (β = 0.33, p < 0.01). The study highlights the importance of embedding CSR in main strategies, adopting a stability reporting framework, and engaging attractive stakeholders to align with national stability goals such as UAE Vision 2021 and the UAE Green Agenda. Recommendations are provided for financial institutions and policymakers to strengthen CSR practices, while future research instructions are suggested to detect field-specific and technology-operated CSR initiatives. This research contributes to the understanding of CSR’s strategic role in achieving sustainable development in the UAE.